Językowe wykładniki obrazu kobiety w "Regule polskiej zakonu panny św. Klary" - na podstawie odpisu z XV/XVI wieku = Linguistic exponents of the image of women in the "Rule of the Polish Order of the Maiden of St. Clare" - based on a copy from the 15th/16th century - Szagun, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this text is to analyze the names and terms of women in the manuscript of the "Rule of the Polish Order of the Maiden of St. Clare" from the 16th century. The analysis is to emerge a linguistic vision of the community of women as seen through the lens of the consensual life of women in a closed monastic community. The choice of linguistic means is further controlled by the pragmatic function of the normative text and linguistic conventionalization procedures resulting from the use of religious style.
Keywords: nazywanie kobiet; reguła zakonna; naming of the woman; religious rule